Writing America : literary landmarks from Walden Pond to Wounded Knee, a reader's companion - Fishkin, Shelley Fisher (Rutgers University Press, 2015)
""A book that redraws the literary map of the United States.""--Junot Díaz Writing America takes readers on an eclectic tour of historic sites that have been pivotal to the making of American literature, reflecting the true diversity of the nation and its authors. Profusely illustrated, it is the literary gift book for 2015.